2016
DOI: 10.1192/bjpo.bp.115.002303
|View full text |Cite
|
Sign up to set email alerts
|

Auditory verbal hallucinations in first-episode psychosis: a phenomenological investigation

Abstract: BackgroundIn dimensional understanding of psychosis, auditory verbal hallucinations (AVH) are unitary phenomena present on a continuum from non-clinical voice hearing to severe mental illness. There is mixed evidence for this approach and a relative absence of research into subjective experience of AVH in early psychosis.AimsTo conduct primary research into the nature of subjective experience of AVH in first-episode psychosis.MethodA phenomenological study using diary and photo-elicitation qualitative techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 42 publications
5
43
3
Order By: Relevance
“…Whilst Jaspers was writing about the phenomenology and subjective patient experiences, of distress, delusional mood and the need for resolution, there is a wealth of information now available that builds on this in our understanding of the context in which delusional beliefs are formed; within the context of a change in brain function. In keeping with the tenant of this chapter, however, it should be noted that these changes are not necessarily specific to delusions over and above other positive symptoms; hallucinations may equally be attributable to dopamine activation independent of cue, with that cue being our own inner speech and salience network dysfunction, or the failure to down regulate the default mode network result internal processes being experienced as heard perceptions (Upthegrove, Ives, et al, 2016). The intricate need for understanding hallucinations and delusions together remains prominent.…”
Section: Sa Writesmentioning
confidence: 84%
See 1 more Smart Citation
“…Whilst Jaspers was writing about the phenomenology and subjective patient experiences, of distress, delusional mood and the need for resolution, there is a wealth of information now available that builds on this in our understanding of the context in which delusional beliefs are formed; within the context of a change in brain function. In keeping with the tenant of this chapter, however, it should be noted that these changes are not necessarily specific to delusions over and above other positive symptoms; hallucinations may equally be attributable to dopamine activation independent of cue, with that cue being our own inner speech and salience network dysfunction, or the failure to down regulate the default mode network result internal processes being experienced as heard perceptions (Upthegrove, Ives, et al, 2016). The intricate need for understanding hallucinations and delusions together remains prominent.…”
Section: Sa Writesmentioning
confidence: 84%
“…In a phenomenological study investigating the subjective experience of voice hearing in 25 young people with first episode psychosis, first person accounts show that hallucinations were characterized by an experience of entity: as though from a living being with complex social interchange and control. Voices were often percived as speaking as an expert authority, able to control individuals, received with passivity and accompanied by sensation in other modalities (Upthegrove, Ives, et al, 2016). Thus, is not surprising that delusional beliefs of communication or possession were a common accompaniment such experiences.…”
Section: Delusions and Hallucinations: Positive Symptomsmentioning
confidence: 99%
“…While we estimated that close to half of all auditory impressions were "heard" in the dream, the acoustic qualities of the second half could not be, or were not, described, and a small subset apparently were only thought-like. This variety of auditory qualities may resemble that seen for hallucinations in psychosis, which include instances that are literally auditory, a mix of auditory and thought-like, and exclusively thought-like [36][37][38][39][40][41]. Already since Kraepelin, it repeatedly has been reported that qualities of verbal hallucinations vary and often are difficult to describe, with variants including «resonant voices», «voices of conscience», «voices which do not speak with words», «an inward voice in the thoughts, «something between hearing and foreboding», and «thoughts circulating in the air» [36,39,42].…”
Section: Plos Onementioning
confidence: 86%
“…As Davies (2017, this issue) points out in his commentary, the potential mechanisms mediating a connection between childhood trauma and the development of psychotic illness are myriad and not necessarily causal: for example, parental mental illness during childhood and prodromal developmental anomalies might increase vulnerability to childhood trauma. Coughlan & Cannon discuss a model where psychotic experiences are triggered and then maintained by traumatic experiences, and in their discussion of psychodynamic perspectives they are led to the suggestion that auditory hallucinations in psychosis could be considered a dissociative phenomenon with a traumatic aetiology, although this is only one of many potential cognitive neurobiological models discussed in the literature (Upthegrove 2016b).…”
Section: Causal Associationsmentioning
confidence: 99%